Designed metal-organic π-clusters combining the aromaticity of the metal cluster and ligands for a third-order nonlinear optical response - Wang, Zirui; Yan, Yayu; Chen, Jiali; Li, Qiao-Hong; Zhang, Jian (Materials horizons, 2024)
The pivotal role of clusters and aromaticity in chemistry is undeniable, but there remains a gap in systematically understanding the aromaticity of metal-organic clusters. Herein, this article presents a novel metal-organic π-cluster, melding both metal-organic chemistry and aromaticity, to guide the construction of structurally stable Os-organic π-clusters. An in-depth analysis of these clusters reveals their bonding attributes, π-electronic composition, and origins of aromaticity, thereby confirming their unique metal-organic π-cluster properties. Furthermore, the Os 5 cluster exhibits a promising third-order nonlinear optical (NLO) response, attributable to its narrow band gap and uniform electron/hole distribution, suggesting its potential as an optical switching material. This research introduces a fresh perspective on clusters, centered on delocalization, and broadens the domain of aromaticity studies. It also presents a novel method for designing efficient third-order NLO materials through consideration of the structure-activity relationship. "Metal-organic π-clusters" were proposed, combining the π-electrons of both the cluster core and ligand for significant applications in third-order nonlinear optical materials.